Hubungan Metode Penugasan Tim Dengan Kepuasan Kerja Perawat Di RS Dustira - Setiawati, Setiawati; Rohayani, Lilis; Airiza Zahara Fauzia, Zia (Jurnal Keperawatan Komplementer Holistic, 2023)
The impact if the team method is not implemented in accordance with the SOP (Standard Operating Procedure) and the dissatisfaction of the nurses is not met, it will make the performance provided by the nurses to the patients not optimal and will make the patients uncomfortable so that it will affect the image of the hospital. Based on the results of a preliminary study at the Dustira TK II Hospital 03.05.01 it was found that the implementation of the team assignment method was not optimal due to the limited number of nurses. In addition, the work carried out is not in accordance with the jobdesk, this is because nurses are required to be able to master all fields related to nursing. This study aims to determine the relationship between the team assignment method and the job satisfaction of nurses at TK II 03.05.01 Dustira Hospital. The research design used was an analytic survey with a cross-sectional approach. The number of samples used was 49 people using a stratified random sampling approach. The results showed that 27 respondents (55.1%) said that the team method was appropriate. As many as 14 respondents (28.6%) were satisfied with their work. The results of the chi square test obtained p value = 0.002, this means that there is a relationship between the team assignment method and the job satisfaction of nurses at the TK II Hospital 03.05.01 Dustira.